Resiliensi Sosial Eks Pekerja Migran Indonesia (PMI) dalam Menghadapi Tantangan Degenerasi Petani - Iskandar, Hadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Farmer degeneration becomes a challenge for the integration of the farming community in Tanjakan Village, Krangkeng District, Indramayu Regency due to the high migration activity of young people to improve their economic and social status. This article aims to analyze in more depth the social resilience of former Indonesian Migrant Workers (PMI) in facing the challenges of farmer degeneration. The concept of social resilience is used to explore the social actions of former PMI in maintaining the integration of their social system. This study uses a qualitative method with a case study approach. The results of the study show that: First, farmer degeneration poses challenges to the social system such as the composition of the non-ideal social class structure, the fading of mutual cooperation values, and the scarcity of farmer labor. Second, the social actions of former PMI have an impact on the social system such as the existence of the middle class, strengthening of patron-client relationships, and alternative livelihood capital for the community. Third, analytically, the social actions of former PMI are a pattern of adaptation to the challenges of farmer degeneration so that social reintegration continues to occur even though the status quo of the previous system has begun to fade.